Pengaruh Kualitas Sistem Drainase Terhadap Pengendalian Banjir Dengan Efektivitas Pengelolaan Air Hujan Dikota Pematangsiantar Kelurahan Bp Nauli - Ndruru, Fransiskus Odaligo; Hani, Sheila; Nasution, Ridwan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Urban drainage is an infrastructure that functions to drain excess water, manage or control surface water, in urban areas. Basically, the drainage system functions to manage excess water by infiltrating as much water as possible into the ground naturally or flowing water to a place (river or sea) without exceeding the capacity of the existing channel or cross-section. In line with population growth and density, drainage problems have become very complex. These drainage problems require an integrated management pattern, both from the drainage aspect (disposal of excess water) and water pollution due to waste and garbage. As a low-lying sub-district, BP Nauli Village, Marihat District is not immune to the threat of flooding that can occur at any time. The flooding that hit several areas in the surrounding sub-district was partly caused by a poorly functioning drainage system. Insufficient drainage channel capacity resulted in slow water discharge so that flooding persisted longer. From the data obtained, it was known that the condition of the drainage channel starting from the BP Nauli Village office was still in fairly good condition, but there were several locations of flooding that occurred in the surrounding residential areas. The purpose of this community service activity is to address the partners' challenges related to drainage channel planning, with the hope of improving the lives of the surrounding community and preventing flooding that can damage roads. The main problem arises from a lack of environmental protection and proper drainage. The proposed solution is comprehensive drainage channel planning.